2016
DOI: 10.1093/cercor/bhw391
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Guided Stumbling Correction in the Hindlimb of Quadrupeds Relies on Parietal Area 5

Abstract: In complex environments, tripping over an unexpected obstacle evokes the stumbling corrective reaction, eliciting rapid limb hyperflexion to lift the leg over the obstruction. While stumbling correction has been characterized within a single limb in the cat, this response must extend to both forelegs and hindlegs for successful avoidance in naturalistic settings. Furthermore, the ability to remember an obstacle over which the forelegs have tripped is necessary for hindleg clearance if locomotion is delayed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…However, neurons exhibiting sustained delay period modulation represent a specialized subset of area 5 neurons capable of maintaining stable representations of obstacle infor-mation in WM. As previous work demonstrated WM deficits precluding successful avoidance when a comparable region of area 5 was deactivated [9,10,28], neurons capable of stable WM maintenance are most likely necessary for such behaviors.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, neurons exhibiting sustained delay period modulation represent a specialized subset of area 5 neurons capable of maintaining stable representations of obstacle infor-mation in WM. As previous work demonstrated WM deficits precluding successful avoidance when a comparable region of area 5 was deactivated [9,10,28], neurons capable of stable WM maintenance are most likely necessary for such behaviors.…”
Section: Discussionmentioning
confidence: 88%
“…For example, area 5 neurons that respond to passive joint manipulation are even more responsive during active movements, demonstrating an integration of both sensory and motor inputs [40]. Correspondingly, previous work has demonstrated that, in comparison to trials where the animal is delayed just before the forelegs have stepped over an obstacle, obstacle memory is more robust when the animal is delayed after foreleg clearance [10,41]. These studies suggest that efference copies of motor commands for elevated foreleg stepping, the resulting proprioceptive feedback, or both are important for WM-guided obstacle locomotion.…”
Section: Parietal Area 5 Contributes To Complex Locomotionmentioning
confidence: 93%
See 3 more Smart Citations